Một megastigman glycozit mới từ lá cây đề Ficus religiosa L. (Moraceae) - Ính và cộng sự, Cầm Thị (Vietnam Journal of Chemistry, 2014)
Phytochemical investigation on Ficus religiosa L. growing in Vietnam led to the isolation of a new megastigmane glycoside   (3S,5R,6R,7E,9R)-megastigman-7-ene-3,5,6,9-tetrol-9-O-b-D-apiofuranosyl-(1''® 2’)-O-b-D-glucopyranoside (I). Its structure has been determined from spectroscopic data including 1- and 2-dimensional NMR, and HR-MS spectra in comparison with the literature.